1940
DOI: 10.1007/bf01984136
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of colours in phaseolus vulgaris L.I.

Abstract: IntroductionThe last eight years I have investigated a great number of bean crosses: over 70 between 26 different types or races. In 19341 published the analysis of the cross of ,,Wagenaar" with ,,Fijne tros". In order to bring my later results in connection with this first analysis I have crossed both races with most of the other types: Wagenaar with 21, Fijne tr0s with 17. From the beginning it has been my endeavour to draw a parallel between the extensive results of a few earlier investigators (e.g. VoH TSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1953
1953
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…In Arabidopsis, some mutations have caused reductions in proanthocyanin content, while others have shown reduction in both anthocyanins and proanthocyanins (Shirley et al, 1995). In common bean, the P locus is a major gene for lack of seed colouration (Prakken, 1970) and has been postulated to regulate the biosynthetic pathways of flavan-3-ols and anthocyanins (McClean, Lee, Otto, Gepts, & Bassett, 2002). However, the recessive allele p produces white seed coats with no condensed tannins or anthocyanins (Erdmann, Lee, Bassett, & McClean, 2002).…”
Section: Anthocyanin Contents and Distributionmentioning
confidence: 99%
“…In Arabidopsis, some mutations have caused reductions in proanthocyanin content, while others have shown reduction in both anthocyanins and proanthocyanins (Shirley et al, 1995). In common bean, the P locus is a major gene for lack of seed colouration (Prakken, 1970) and has been postulated to regulate the biosynthetic pathways of flavan-3-ols and anthocyanins (McClean, Lee, Otto, Gepts, & Bassett, 2002). However, the recessive allele p produces white seed coats with no condensed tannins or anthocyanins (Erdmann, Lee, Bassett, & McClean, 2002).…”
Section: Anthocyanin Contents and Distributionmentioning
confidence: 99%
“…Mature dry seeds used for planting were used to classify seed color, which was further classified by putative genotype in relation to known genes affecting color and patterning, or modifying color intensity or shades. Genotypic determination was based on a combination of observed flower and seedcoat color using Prakken (1934Prakken ( , 1940Prakken ( , 1970Prakken ( , 1972aPrakken ( , 1972bPrakken ( , 1974 and Bassett (2007) to associate genes to observed phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…Starch hydrolysis is one of the most conspicuous changes that characterizes ripening of some climacteric fruits. This change is more evident in banana where starch concentration drops in a few days from an average of 22% in the preclimacteric phase to less than 1% at the climacteric peak (8 ). Phosphorylase and amylase have been detected in many storage tissues of many fruits but the 'Received tor publication September 12.…”
Section: Abstract Starch H Yd Rolysis P H Osp H Orylase P H Osp Hatas...mentioning
confidence: 99%
“…The inheritance of seed-coat color has been investigated in beans (Phaseolus vulgaris) by several researchers (6,7,8,9,10) and reviewed by Yarnell (13). Lamprecht and Randall (6) reported that seed-color in P. vulgaris was due to a major dominant gene P along with dominant genes for color.…”
mentioning
confidence: 99%